The Effect of Village Fund Policy on Indonesia’s Poverty Rate (Study with Mixed Methods Approach) - Ndun, Anggri Kristiyanto Yofen; Moeis, Jossy Prananta (SEAN Institute, 2024)
The aim of this study is to determine the effect of the Village Fund policy on poverty rates in Indonesia using the head count index (P0), poverty gap index (P1) and poverty severity index (P2), by applying a combination of quantitative and qualitative methods. The quantitative phase uses a panel data model at the district/city level that receives village fund policies in the span of 2015 – 2020, while a case study in Kenebibi Village in Belu Regency, East Nusa Tenggara Province (sample village) serves as the qualitative phase. Based on the estimation results of the fixed effect model, the village fund policy is statistically proven to reduce P0 but has no effect on P1 and P2. This results were then confirmed through the findings of qualitative research, which shows that the priority programs of the village fund policy in the form of development and community empowerment had not fully benefited the poor of the village, especially the lowest poor groups. Thus, the poverty gap and the severity of poverty could not be solved by village funds. The results of this study suggest that the government needs to evaluate the formulation of village fund allocations by taking into account the gap and severity of poverty, considering the existence of marginal communities as village characteristics, including involving the lowest poor community groups in the village.